Pade–Chebyshev Approximants for One Class of Functions - Holub, A. P. (Ukrains’kyi Matematychnyi Zhurnal, 2002)
By using the method of generalized moment representations proposed by Dzyadyk in 1981, we construct the Pade–Chebyshev approximants for one class of functions that is an analog of the class of Markov functions.